TaUGT6, a Novel UDP-Glycosyltransferase Gene Enhances the Resistance to FHB and DON Accumulation in Wheat - He, Yi; Wu, Lei; Liu, Xiang; Jiang, Peng; Yu, Lixuan; Qiu, Jianbo; Wang, Gang; Zhang, Xu; Ma, Hongxiang (Frontiers in Plant Science, 2020)
Fusarium head blight (FHB), a devastating wheat disease, results in loss of yield and production of mycotoxins including deoxynivalenol (DON) in infected grains. DON is harmful to human and animal health and facilitates the spread of FHB symptoms. Its conversion into DON-3-glucoside (D3G) by UDP-glycosyltransferases (UGTs) is correlated with FHB resistance, and only few gene members in wheat have been investigated. Here, Fusarium graminearum and DON-induced TaUGT6 expression in the resistant cultivar Sumai 3 was cloned and characterized. TaUGT6::GFP was subcellularly located throughout cells. Purified TaUGT6 protein could convert DON into D3G to some extent in vitro. Transformation of TaUGT6 into Arabidopsis increased root tolerance when grown on agar plates containing DON. Furthermore, TaUGT6 overexpression in wheat showed improved resistance to Fusarium spread after F. graminearum inoculation. Overall, this study provides useful insight into a novel UGT gene for FHB resistance in wheat.